Technical quality of root canal treatment performed by undergraduate students using rotary instruments versus hand instruments: A Retrospective Study - Seyda Ersahan; Nur Sena Arıkan; Yelda Erdem Hepşenoğlu; Alperen Tekin (Selçuk University, 2023)
Background: The technical quality of root canal treatment (RCT) may impact on the outcome. The quality of education received during undergraduate school may be linked to the quality of treatment provided in general dental practice. Objective: To compare the technical quality of RCT where rotary or manual step-back canal preparatory technique was employed in an undergraduate dental clinic in Turkey. Additionally, the present study aimed to compare radiographically commonly seen complications in both instrumentation systems. Materials and Methods: Dental records of 270 patients who received RCT undertaken by dental students were investigated by retrospective chart review. 565 root canals belonging to 270 patients were randomized into two groups [(rotary, n=280, and manual hand instruments, n=285)]. Root canal obturation was evaluated on the basis of the length of obturation being >2mm from the radiographic apex, with uniform radiodensity and good adaptation to root canal walls. Inadequate root canal obturation included cases containing procedural errors such as perforation, ledge, transportation, instrument separation. Descriptive statistics were used to define categorical variables (n, %) and the level of significance was set at 0.05. Results: The technical quality of RCT performed by undergraduate dental students was classified as 'adequate' in 75% and 53.7% of the cases, respectively for rotary and manual groups, respectively (p < 0.05). The highest procedural errors were seen in molars. Occurrence of procedural errors differed significantly between the groups, being 6.4% in rotary group and 12.3% in manual group (p = 0.017). However, occurrence of ledge formation was higher in manual group than that of rotary group (p = 0.007). Conclusion: In view of our findings, RCT performed by undergraduate dental students using rotary instrumentation systems is of higher technical quality and also has fewer procedural errors than manual instrumentation.